Palmitoylation-mediated synaptic regulation of AMPA receptor trafficking and function - Sohn, Heesung; Park, Mikyoung (PHARMACEUTICAL SOC KOREA, 2019)
The -amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) is a major glutamate-gated ion channel in the brain and is important for synaptic transmission, synaptic plasticity, and learning. Palmitoylation, a post-translational modification, is a critical process regulating AMPAR trafficking, synaptic function and plasticity, and learning and memory in health and diseases. In this review, we discuss current knowledge on the palmitoylation-dependent regulation of AMPAR trafficking and functions. We focus on the palmitoylation of AMPARs and other synaptic proteins that directly or indirectly interact with AMPARs, including postsynaptic density 95, glutamate receptor-interacting protein/AMPAR-binding protein, A-kinase anchoring protein 79/150, and protein interacting with C kinase 1. Finally, we discuss what future studies should address in the field of palmitoylation-dependent AMPAR trafficking and function with regard to physiology and neurodegenerative diseases.
Keywords: ACTIVITY-DEPENDENT UBIQUITINATION; DOMAIN-CONTAINING PROTEIN; MOUSE MODEL; DIFFERENTIAL PALMITOYLATION; INTRACELLULAR TRAFFICKING; PHOSPHORYLATION SITES; POSTSYNAPTIC DENSITY; GLUTAMATE RECEPTORS; DUAL PALMITOYLATION; SUBUNIT COMPOSITION